The Role of Oil Prices and Monetary Policy in the Norwegian Economy Since the 1980s - Q. Farooq Akram; Haroon Mumtaz (Norges Bank, 2016)
We use a TVP-VAR model to investigate possible changes in the time series properties of key Norwegian macroeconomic variables since the 1980s. The sample period is characterised by deregulation, globalization, sizable petroleum revenues, a switch from exchange rate to inflation targeting and adoption of a policy rule for the use of petroleum revenues.We find that the long-run means of CPI and core inflation rates declined significantly until the mid-1990s and have since then remained close to the inflation target of 2.5% from 2001 onwards. The persistence in especially CPI inflation has fallen during the inflation targeting period while the volatility of both inflation rates and the nominal effective exchange rate has increased. We document an increase in the correlations between money market rates and the inflation rates as well as the output gap during the inflation targeting period and a steady decline towards zero in the correlations between money market rates and nominal exchange rate changes. There is evidence of an increase in the correlations between oil prices and the other macroeconomic variables over time. Our counterfactual analysis suggests oil shocks to have been important for output gap and inflation volatility while monetary policy shocks have been important for driving inflation persistence and the correlation of money market rates with macroeconomic variables.
hdl:11250/2495735
Keywords: C51; E31; E32; E52; E58; 330; time-varying coefficients; stochastic volatility; persistence; great moderation; inflation targeting